Little Empire Daycare Management System - Satevello, Maalini; MOHAMAD, Dr. RADIAH (Applied Information Technology And Computer Science, 2025)
The necessity for efficient and transparent daycare management systems has become paramount in today's fast-paced world, where parents seek real-time updates and seamless interactions with childcare providers. The Daycare Management System (LE-DMS) developed for Little Empire Childcare Centre aims to address the inefficiencies of traditional childcare management by integrating advanced web-based technologies. This system is engineered using the Waterfall development methodology to ensure a structured and phased implementation. The core functions of LE-DMS include attendance management, which allows administrators to mark students as present or absent, record complete records, and allow parents to access and download their child's attendance history, as well as faster invoicing processes and activity updates. This paper explores the system's development process, emphasizing the technological solutions adopted to enhance operational efficiency, parent-admin communication, and overall data management. By automating routine tasks and providing a platform for instant updates and parental engagement, the system optimizes administrative workflows and enriches the childcare experience. The expected outcome is a significant reduction in administrative burdens and an increase in satisfaction levels among staff and parents, paving the way for a more interactive and fulfilling childcare environment